Therapeutic Lowering of C-Reactive Protein - Jimenez, Rachel V.; Szalai, Alexander J. (Frontiers in Immunology, 2021)
In the blood of healthy individuals C-reactive protein (CRP) is typically quite scarce, whereas its blood concentration can rise robustly and rapidly in response to tissue damage and inflammation associated with trauma and infectious and non-infectious diseases. Consequently, CRP plasma or serum levels are routinely monitored in inpatients to gauge the severity of their initial illness and injury and their subsequent response to therapy and return to health. Its clinical utility as a faithful barometer of inflammation notwithstanding, it is often wrongly concluded that the biological actions of CRP (whatever they may be) are manifested only when blood CRP is elevated. In fact over the last decades, studies done in humans and animals (e.g. human CRP transgenic and CRP knockout mice) have shown that CRP is an important mediator of biological activities even in the absence of significant blood elevation, i.e. even at baseline levels. In this review we briefly recap the history of CRP, including a description of its discovery, early clinical use, and biosynthesis at baseline and during the acute phase response. Next we overview evidence that we and others have generated using animal models of arthritis, neointimal hyperplasia, and acute kidney injury that baseline CRP exerts important biological effects. In closing we discuss the possibility that therapeutic lowering of baseline CRP might be a useful way to treat certain diseases, including cancer.